2022
DOI: 10.3389/fpubh.2022.787135
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of digital health interventions: A systematic review of the literature

Abstract: BackgroundDigital health interventions have significant potential to improve safety, efficacy, and quality of care, reducing waste in healthcare costs. Despite these premises, the evidence regarding cost and effectiveness of digital tools in health is scarce and limited.ObjectivesThe aim of this systematic review is to summarize the evidence on the cost-effectiveness of digital health interventions and to assess whether the studies meet the established quality criteria.MethodsWe queried PubMed, Scopus and Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 47 publications
(238 reference statements)
4
55
0
Order By: Relevance
“…Digital interventions, including smartphone apps, websites, and SMS text messaging interventions, have proven efficacious for a wide variety of behavioral health outcomes, including mental health, diet, exercise, and smoking cessation [ 1 - 6 ]. An important value of digital interventions for behavioral health is that they are accessible at a low cost, thereby increasing their potential public impact and reducing disparities in behavioral health care [ 7 - 9 ]. An ongoing central challenge to the overall efficacy and broadly scalable implementation of digital interventions is the phenomenon of users dropping out early [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital interventions, including smartphone apps, websites, and SMS text messaging interventions, have proven efficacious for a wide variety of behavioral health outcomes, including mental health, diet, exercise, and smoking cessation [ 1 - 6 ]. An important value of digital interventions for behavioral health is that they are accessible at a low cost, thereby increasing their potential public impact and reducing disparities in behavioral health care [ 7 - 9 ]. An ongoing central challenge to the overall efficacy and broadly scalable implementation of digital interventions is the phenomenon of users dropping out early [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While it is true that the development of the mobile app was expensive initially, after initial deployment this sort of app can be inexpensive to maintain while providing access to large numbers of patients. We 106 and others 107 have shown that initial development and ongoing deployment costs can be substantially offset by benefits such as improved selfmanagement behavior. Lindsay et al, 61 for example, showed that a substantial increase in activation was associated with lower follow-up costs, especially in high risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health interventions and self-monitoring offer quick, cost-effective, personalized, accessible medical care and nutritional advice[ 53 ]. Especially when considering the rising number of IBD patients and an insufficient number of specialists, telemedicine could reduce the burden on the healthcare system by providing digital sources.…”
Section: Discussionmentioning
confidence: 99%